Semiquantified Noncalcified Coronary Plaque in Systemic Lupus Erythematosus - KIANI, ADNAN N. (2012)
OBJECTIVE: A major cause of morbidity and mortality in systemic lupus erythematosus (SLE) is accelerated coronary atherosclerosis. New technology (computed tomographic angiography) can measure noncalcified coronary plaque (NCP), which is more prone to rupture. We report on a study of semiquantified NCP in SLE. METHODS: Patients with SLE (n = 147) with no history of cardiovascular disease underwent 64-slice coronary multidetector computed tomography (MDCT). The MDCT scans were evaluated quantitatively by a radiologist, using dedicated software. RESULTS: The group of 147 patients with SLE was 86% female, 70% white, 29% African American, and 3% other ethnicity. The mean age was 51 years. In our univariate analysis, the major traditional cardiovascular risk factors associated with noncalcified plaque were age (p = 0.007), obesity (p = 0.03; measured as body mass index), homocysteine (p = 0.05), and hypertension (p = 0.04). Anticardiolipin (p = 0.026; but not lupus anticoagulant) and anti-dsDNA (p = 0.03) were associated with higher noncalcified plaque. Prednisone and hydroxychloroquine therapy had no effect, but methotrexate (MTX) use was associated with higher noncalcified plaque (p = 0.0001). In the best multivariate model, age, current MTX use, and history of anti-dsDNA remained significant. CONCLUSION: Our results suggest that serologic SLE (anti-dsDNA) and traditional cardiovascular risk factors contribute to semiquantified noncalcified plaque in SLE. The association with MTX is not understood, but should be replicated in larger studies and in multiple centers.